The prognostic value of rectal invasion for stage IVA uterine cervical cancer treated with radiation therapy - Wakatsuki, Masaru (BMC Cancer, 2016)
BACKGROUND: The prognostic value of rectal invasion is still unclear in stage IVA cervical cancer. The objective of this study is to evaluate patient outcome and prognostic factors in stage IVA cervical cancer treated with radiation therapy. METHODS: A retrospective review of the medical records of patients treated with definitive photon radiation therapy for pathologically proven stage IVA cervical cancer between 1980 and 2010 was performed. Eligible patients for the present study were diagnosed with clinical stage IVA cervical cancer by cystoscopy or/and proctoscopy, and they received definitive radiation therapy consisting of a combination of external beam radiotherapy and high-dose-rate brachytherapy. All patients underwent CT scans of the abdomen and pelvis. RESULTS: Among the 67 stage IVA patients studied, 53 patients were stage IVA on the basis of bladder invasion, 7 according to rectal mucosal invasion, and 7 because of both bladder and rectal mucosal invasion. Median follow-up of all patients and surviving patients was 19 months (range, 2–235 months) and 114 months (range, 14–223 months), respectively. The 5-year local control (LC), disease-free survival (DFS), and overall survival (OS) rate were 55, 17, and 24 %, respectively. Rectal invasion had significant impact on DFS, but bladder invasion had the opposite effect (p = 0.00006 and 0.005, respectively). There were significant differences of LC, DFS and OS rates between patients with and without rectal invasion (p = 0.006, 0.00006 and 0.05, respectively). CONCLUSIONS: Patients with stage IVA cervical cancer had poor prognosis, with 5-year survival of only 24 %. Furthermore, in stage IVA, rectal invasion might be a worse prognostic factor than bladder invasion.